Feelings experienced after previous suicide attempt by the individual and the reaction of close relatives or friends to previous attempt. (1st March 2011) - de Silva, P; de Silva, D; Jayasinghe, S; de Alwis Seneviratne, R; Abeyratne, M; Rajapakse, D; Mendis, N
Abstract : Introduction: The feelings experienced after a suicide attempt by the individual and the reaction of close relatives or friends to attempt is important in designing preventive mechanisms. Objective: To describe the experience of the patient after the previous suicide attempt and the reaction of close relatives or friends to the previous suicide attempt. Method: From 668 presented with attempted suicides presented to National Hospital of Sri Lanka (April to December 2002), 300 were randomly selected and interviewed using a pretested questionnaire. Results: Previous suicidal attempts were present in 29 (9.7%) out of total 300 attempted suicides. The feelings following the previous suicide attempt were as follows: 19 felt pity (65.5%), 16 felt embarrassed (55.2%), 13 felt ashamed (44.8%), 11 felt afraid (37.9%), 10 felt angry (34.5%), 4 felt released (13.8%) and 2 felt proud (6.9%). Regarding reaction of close relatives or friends to last attempt, 25 (86.2%) of patients felt that others showed pity for patient, 11 (45.8%) patients felt that some people showed understanding, 16 (57.1%) felt that no one showed anger or irritation, 21 (75%) felt that others did not show embarrassment or avoided them, 24 (85.7%) felt no body laughed at them, 23 (82.1%) felt others did not ignore them. Conclusion: The feeling following the suicidal attempts was of shame and embarrassment. The close relatives or friends of attempted suicides do not show negative emotions.